Assessing respiratory contributions to f0 declination in German across varying speech tasks and respiratory demands. (September 2015) - Fuchs, Susanne; Petrone, Caterina; Rochet-Capellan, Amélie; Reichel, Uwe D.; Koenig, Laura L.
Abstract: Many past studies have investigated the factors that affect f 0 declination and its physiological underpinnings. This study assessed the relation between respiration and f 0 declination by means of simultaneous acoustic and respiratory recordings of read and spontaneous speech from speakers of German. We analysed the effect of the number of syllables and voiceless obstruents within each Intonational Phrase unit. Both factors could influence the slope of f 0 declination and/or rib cage movement. If respiration and f 0 declination are related physiologically, their relationship might also be modulated by either or both factors. Our results show consistently, for read and spontaneous speech, that the slope of the rib cage movement is not related to f 0 declination. F 0 slopes are shallower in spontaneous than in read speech. F 0 declination was affected by utterance length, but rib cage slope was not. Finally, although a higher number of voiceless obstruents yielded a greater rib cage compression, it did not affect f 0 declination. These results suggest that although f 0 declination occurs in many languages, it might not have a purely physiological origin in breathing. Other factors such as speech planning and communicative constraints might interact with physiological constraints to shape f 0 declination. Highlights: We study f 0 declination in relation to respiration and utterance length. Read and spontaneous speech corpora were compared. F 0 declination is independent of rib cage changes and number of voiceless obstruents. F 0 declination systematically varies with utterance length. The magnitude of such an effect depends on the speech task.